Supercritical Carbon Dioxide Extraction of Leucaena leucocephala Podâ€“ Oil Yield & Component Identification - A.Zainuddin, N.; Subuki, Istikamah; A. Ibrahim, K.; Fariza Ismail, Nor; Rohana Mohd Yatim, Siti; Harliza Abd Razak, Noor (International Journal of Engineering and Technology, 2018)
Relatively previous researches on Leucaena Leucocephala (L.leucocephala) were undergone by using traditional method such as hydrodistillation and soxhlet extraction methods which have their own disadvantages such as long extraction time and non-solvent free oil extract. Thus, a clean extraction method of supercritical fluid extraction (SFE) method using supercritical carbon dioxide (SC-CO2) with ethanol as co-solvent was proposed for the extraction of L.leucocephala pods to produce oil with pharmaceutical components. The SC-CO2 extraction of L.leucocephala was studied by using measurement of yield of oil extracted and component identification. The extraction was conducted at constant CO2 flowrate of 24mL/min and constant ethanol flowrate of 2.4mL/min at extraction time of 60 minutes within a range of temperature (40Â°C, 50Â°C and 60Â°C) and range of pressure (3000, 4000, 5000, 6000, 7000 psi). The component in L.leucocephala oil with the highest oil yield was determined using Gas Chromotography-Mass Spectrometry (GC-MS). The highest extraction oil yield of 4.92% (g oil/ g sample) was obtained at pressure 6000 psi and temperature 60Â°C. The component in the oil extract with the highest oil yield was determined based on the major components identified comprised of pentanoic acid, phosphonic acid, ecgonine, oleic acid and octadecadienoic acid.Â Â